NORTH-CAUCASUS AND OTHER FRONTIERS OF RUSSIA: HISTORICAL AND COMPARATIVE ANALYSIS - Magaramov, Sarafutdin Arifovic; Seferbekov, Magomedhabib Ruslanovic (History, Archeology and Ethnography of the Caucasus, 2024)
The applicability of the frontier concept to the North Caucasus has been repeatedly proposed and substantiated within scholarly literature, including international sources. However, some researchers contest the frontier interpretation of the historical process of Caucasian incorporation into the Russian Empire, particularly objecting to the application of the classical (Turner’s) frontier model to the history of the North Caucasian peoples. This study aims to examine the commonalities and differences between the North Caucasian borderland and other contemporaneous Russian frontier zones, most notably the Siberian and southern frontiers. Comparing the latter with the North Caucasian case allows for the application of established methodological approaches from Siberian and South Russian historiography to the North Caucasian region. This comparison reveals the unique and distinct historical characteristics of each region, contributing to frontier theory by prompting investigation into the causes of similarities, differences, and evolutionary trajectories of Russian frontier territories. The study’s methodological foundation is the comparative historical method, incorporating the frontier concept as an integral analytical framework. This research demonstrates that the North Caucasian frontier possesses several distinguishing characteristics that set it apart from other Russian contact zones, contributing to its unique character, despite consistent interactions with the Russian state. A comparative study of the North Caucasian frontier with other Russian border zones reveals distinct characteristics such as polyfrontierism, its nature as a religious borderland, and the absence of a “no man’s land.” These features warrant further investigation and promise to enhance our understanding of how Russian influence was established in the North Caucasus. Similarities observed across these frontiers include the concurrent development and demarcation of state borders, the common practice of Cossack settlement as a vanguard of Russian colonization, and the element of coercion in settler presence within these frontier zones.